NIGERIA ECONOMIC GROWTH: THE QUEST FOR GLOBALIZATION - Ogu, Callistus (African Journal of Social and Behavioural Sciences, 2024)
This study analyzed globalization’s influence on Nigeria’s economic expansion from 1986 to 2022. The study obtained the data from the CBN Statistical Bulletin (2022) and the World Development Indicator (2022). The variables of interest in this study were the Gross Domestic Product Growth Rate (GDPGR), which was the dependent variable, and globalization (GLOB), represented by trade openness, Balance of Payment (BOP), and Exchange Rate (RER), which were the explanatory factors. The Augmented Dickey-Fuller (ADF) test was employed to determine the stationarity of the model, revealing that the variables exhibited a mixed order. The ARDL co-integration boundaries test was used to determine the long-term link between the variables. The analysis revealed the existence of co- integration, thereby confirming a relationship between globalization indicators and economic growth in Nigeria, both in the short and long term. The findings demonstrated a clear and substantial correlation between globalization and economic growth in Nigeria. Additionally, the balance of payments exhibits a positive and significant correlation with economic growth in Nigeria, and the exchange rate exhibits a positive and insignificant relationship with economic growth in Nigeria. In conclusion, the study found that globalization significantly impacts economic growth, which aligns with the orthodox perspective. It was recommended that policy guidelines that would foster trading opportunities in foreign markets are necessary to enhance globalization in the country.